Mourning between ancient and recent understanding: A comparative study showing the prohibitions upon the mourning woman according to the school of Imaam Al Shaafiyy: - Abu Zaki, Rana Nabil (Journal of Islamic Sciences, 2022)
This research aims to shed light on one of the Islamic jurisprudence rules related to women, specifically widowed women in their post-marital waiting period known as Ihdaad, to know what is permissible for them to do and what is prohibited. This research is significant due to the importance of this rule in preserving women and lineages, while taking the Islamic law into consideration with acceptance and submission. The purpose of this paper is to clarify in detail what a mourning woman must avoid during her post-marital waiting period concerning her attire, fragrance application, makeup, jewelry, and others. Descriptive and comparative analyses were used relying on the hadiths of Prophet MoHammad, peace be upon him, and what our scholars mentioned in their books to explain the terminologies used and the meanings comprised in these hadiths, while illustrating how these scholars used relevant examples to clarify these meanings. Nevertheles, these examples were well-known in their period but very unfamiliar nowadays; for that, a major effort was done depending on early and modern dictionaries, in addition to medical books and other available means, to give a clear explanation of these terminologies in an attempt to relate them to what is recognized today. Had this effort been neglected today, what our scholars had presented for us will be forgotten and become mere ink on paper. Moreover, since the topic of this paper is closely related to the post-marital waiting period and the different statuses of a separated woman, whether by divorce or breach or other, this paper also puts forward a discussion of the rules concerning these issues.